Sharing Affection Between A Father and His Child In Ernest Hemingway’s Short Story A Day’s Wait: A Humanistic Approach Based on Maslow’s Hierarchy of Needs by Abraham Maslow - Tuminah; Kurniawan, Trio (JR-ELT (Journal of Research in English Language Teaching), 2025)
The short story A Day’s Wait by Ernest Hemingway portrays the affectionate relationship between a father and his sick child, reflecting the fulfillment of basic human needs according to Abraham Maslow’s hierarchy of needs theory. This study aims to analyze the father’s expression of affection using Maslow’s humanistic theory approach and to examine the implications of fulfilling the child’s psychological needs in parenting. A qualitative method was employed, involving a literature study and content analysis of the story and supporting literature. Data were collected through a systematic literature review, including relevant quotations from the story and theoretical sources. The analysis identified main themes linked to Maslow’s theory. The results show that the father’s affection fulfills not only the child’s physical needs through medical care but also psychological and emotional needs through presence, communication, and consistent support. Meeting these needs helps the child overcome fear and undergo a holistic healing process. This study contributes to the language and literature fields by enriching the understanding of short story analysis through a humanistic psychology perspective, while emphasizing the importance of emotional aspects in literary interpretation and parenting within a cultural context